Украинская лексика в “Печерских антиках” Николая Лескова - Dzyk, Roman (Ústav slavistyky Filozofické fakulty Masarykovy university, 2020)
The article under discussion considers the history of the study of the peculiarities of Nikolai Leskov’s literary speech, with a special emphasis on its Ukrainian component. The current concepts of revealing, functioning and systematizing the Ukrainian vocabulary in the writer's works are also analyzed. There has been carried out a comparison of the notes to “Pechersky Antics”, pointing to the Ukrainian vocabulary. A number of changes were found in relation to this lexisas a result of comparing the first version, printed in “Kievskaya Starina”, and the edited version in the intravital collected works, which became the basis for all subsequent editions. Cases of the use of Ukrainian vocabulary in “Pechersky Antics” are collected and systematized. The problem of translating this vocabulary into the Ukrainian language on the example of three existing translations is touched upon.
Ukrainian Lexis in “Pechersky Antics” by Nikolai Leskov
Keywords: Николай Лесков; «Печерские антики»; украинская лексика; украинизмы; сказ; перевод; русско-украинские литературные отношения; Nikolai Leskov; “Pechersky Antics”; Ukrainian vocabulary; Ukrainianisms; translation; Russian-Ukrainian literary relations